The physiological determinants of peak power output in sprint cycling - Kordi, M. M. (Northumbria University, 2019)
Sprint cycling represents up to eight medal opportunities at the Olympic Games (six in track cycling and two in BMX). Previous studies and high-resolution data collected from instrumented cranks by practitioners at the English Institute of Sport working at British Cycling have established that peak power output (PPO), which can be defined as the highest mechanical power output produced over a revolution of the pedal cycle, is a significant determinant of sprint cycling performance. Despite this being well-established and considering the number of Olympic medal opportunities in the sprint cycling disciplines, the research investigating the physiological determinants are limited. Of the limited data available, maximal strength has been strongly associated with sprinting ability. Other studies have tried to investigate other putative physiological estimates and their relationship with PPO in isolation, such as muscle architecture, muscle activation and lean leg volume. However, whilst these studies have been valuable in trying to get a better physiological understanding of PPO, none have attempted a multi-faceted approach that examines a number of physiological measurements simultaneously, seldom are they carried out longitudinally and, typically, they use untrained participants or endurance-trained athletes. Thus, the overarching aim of this thesis was to ascertain the physiological determinants of PPO in sprint cycling. The series of investigations that set out to address this aim has led to new data that inform coaches, practitioners and cyclists to better understand how to apply, and potentially optimise, training and improve performance. Study 1 has established between-session reliability for all aspects of the power-cadence (P-C) and torquecadence (T-C) relationships for two separate sprint cycling tests, as well as comparing all the measurements between tests. The findings show that both tests exhibited good between-session reliability, but all P-C and T-C measurements were different between sprint cycling tests. Accordingly, both tests could be used with good between-session reliability but could not be interchanged. Study 2 demonstrated that between-session surface EMG was unreliable when used during sprint cycling assessments and unsuitable to be used to determine any changes between-participants or over time. The main findings from study 3 have confirmed that, of all the major lower body muscle groups, the maximal strength of the knee extensors best predict PPO and therefore, the main physiological determinates of PPO were likely to be rooted in the thigh and more specifically, the knee extensors. However, PPO is better predicted when compared to maximum strength measurements from an isometric maximum voluntary contraction of a cycling-specific isometric task. Study 4 built on the findings of the previous study and focused on a number of physiological measures in the thigh in a broad range of elite level cyclists. The findings suggests that the muscle volume of the quadriceps and the pennation angle of the vastus lateralis best predict PPO in elite cyclists. Lastly, the final study also built on the findings of study 3, which conducted a training intervention that used maximal isometric cycling training to manipulate the P-C and T-C relationship. This was done by increasing the maximal torque of the T-C relationship. Furthermore, sprint cycling training also increased pennation angle of the vastus lateralis and explosive strength at 200 ms. Collectively, this thesis adds to the understanding of the physiological determinants of PPO in sprint cycling. Despite maximal strength, explosive strength, muscle volume and pennation angle all being linked and being predictive of PPO, the underlying mechanisms remain elusive. However, strong evidence is provided that supports the use of a novel training intervention to improve performance in elite sprint cyclists.